Enhancement of Electrochemical Detection of Gluten with Surface Modification Based on Molecularly Imprinted Polymers Combined with Superparamagnetic Iron Oxide Nanoparticles - Dalawan Limthin; Piyawan Leepheng; Annop Klamchuen; Darinee Phromyothin (Polymers, 2021)
Novel molecularly imprinted polymers (MIPs) represent a selectively recognized technique for electrochemical detection design. This rapid and simple method prepared via chemical synthesis consists of a monomer crosslinked with an initiator, whereas low sensitivity remains a drawback. Nanomaterials can improve charge transfer for MIP surface modification in order to overcome this problem. SPIONs have semiconductor and superparamagnetic properties that can enhance carrier mobility, causing high sensitivity of electrochemical detection. In this work, surface modification was achieved with a combination of MIP and SPIONs for gluten detection. The SPIONs were synthesized via the chemical co-precipitation method and mixed with MIPs by polymerizing gluten and methyl methacrylate (MMA), presented as a template and a monomer. Magnetic MIP (MMIP) was modified on a carbon-plate electrode. The morphology of modified electrode surfaces was determined by scanning electron microscopy-energy-dispersive X-ray spectrometry. The performance of the MMIP electrode was confirmed by cyclic voltammetry, amperometry, and electrochemical impedance spectroscopy. The MMIP electrode for gluten detection shows a dynamic linear range of 5-50 ppm, with a correlation coefficient of 0.994 and a low detection limit of 1.50 ppm, which is less than the U.S. Food and Drug Administration requirements (20 ppm); moreover, it exhibits excellent selectivity, sensitivity, stability, and reproducibility.
Keywords: Analytical chemistry methods development; Electrochemical Analysis and Applications; Analytical Chemistry and Sensors